Changing thunderstorms environments in Saudi Arabia: Frequency, variability and drivers of change - Moutassem El Rafei; Andrew Dowdy; Mazen E. Assiri; Md. Arfan Ali; Muhammad Haroon Siddiqui; Sajjad Saeed; Saeed Ahmad Alghamdi; Shamsuddin Shahid (Atmospheric Research, 2026)

Phase-specific effects of guar meal and β-mannanase on growth performance and nutrient digestibility in broilers - Haroon Ur Rashid; Taimoor Khan; Muhammad Tahir; Muhammad Daud; Damiano Cavallini; Giovanni Buonaiuto (Tropical Animal Health and Production, 2026)
This study evaluated the phase-specific effects of dietary guar meal (GM) inclusion, with or without β-mannanase supplementation, on growth performance, nutrient digestibility, and energy utilization in broiler chickens. A total of 300 male Ross 308 broilers were assigned to eight experimental diets in a 4 × 2 factorial arrangement, consisting of four GM inclusion levels (0%, 4%, 8%, and 12%) with or without β-mannanase supplementation (0.35 g/kg), and were evaluated during the starter (7–21 d) and grower (22–35 d) phases. During the starter phase, broilers fed 4% GM supplemented with β-mannanase achieved growth performance comparable to the control diet, whereas increasing GM inclusion significantly reduced body weight gain, crude protein digestibility, and apparent metabolizable energy (AME; P < 0.05). β-mannanase supplementation partially alleviated these negative effects and fully restored crude protein digestibility at 4% GM. During the grower phase, broilers tolerated up to 8% GM without major reductions in growth performance, whereas 12% GM consistently impaired productive responses. Enzyme supplementation further enhanced body weight gain and protein digestibility across GM inclusion levels; however, its efficacy declined at 12% GM, where performance and energy utilization remained significantly lower than the control diet ( P < 0.05). These findings demonstrate that broiler responses to GM are strongly age-dependent and identify phase-specific tolerance thresholds for dietary inclusion. Under the conditions of this study, 4% GM during the starter phase and up to 8% GM during the grower phase can be successfully incorporated when supported by β-mannanase supplementation. This strategy may facilitate the sustainable utilization of guar meal as an agro-industrial by-product while maintaining productive performance and nutrient efficiency in broiler production systems.

Retraction Note: Thymoquinone and Vitamin C Attenuates Pentylenetetrazole-Induced Seizures Via Activation of GABAB1 Receptor in Adult Rats Cortex and Hippocampus - Ikram Ullah; Haroon Badshah; Muhammad Imran Naseer; Hae Young Lee; Myeong Ok Kim (NeuroMolecular Medicine, 2026)

Evaluating the effect of Iron biofortification on nutraceutical and aromatic profiles of cereal grains: A case study of pearl millet - Hamza M.A. Abaker; Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Muhammad Arslan; Gustav Komla Mahunu; Zhuhai Li; Xiaodong Zhai; Abdalbasit Adam Mariod; Mohammad Rezaul Islam Shishir; Magdi Ali Osman Mohammed; Ahmed Gaafar Mohammed Elgorashi; Alaa K.M. Khogly; et al. (Food Chemistry, 2026)

Formulation and Evaluation of Losartan Potassium Microparticles Loaded Controlled-Release Tablets: An In-Vitro Perspective - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Farman Shah; Naveed Ullah; Fida Muhammad; Anam Adil; Sami ul Haq; Haroon Khan (Journal of Pharmaceutical Innovation, 2026)

Spatiotemporal dynamics of historical and future drought conditions over the Arabian Peninsula from ERA5 and CMIP6 data - Muhammad Haroon Siddiqui; Mazen E Assiri; Sajjad Saeed; Md Arfan Ali; Moutassem El Rafei; Shahad Bahamdan; Abdullah Masoud Alqahtani; Abdulrahman AlHaidari; Abdulrahman Alsalhi; Ohood Alzahrani; Shamsuddin Shahid (Journal of Earth System Science, 2026)

Botulinum toxin from foodborne hazard to aesthetic and biomedical tool: mechanisms, applications, detection strategies, and future perspectives - Muhammad Adnan; Muhammad Waqar; Rais Ahmed; Haroon Afzal; Muhammad Abdullah Mueen; Urooj Qayyum; Farhang Hameed Awlqadr; Muhammad Talha Yaqoob; Sabrin R. M. Ibrahim; Gamal A. Mohamed; Iqra Rafiq; Hagar M. Mohamed (Archives of Microbiology, 2026)

Design and development of a low-cost industrial prototype of spot-specific spraying system for potato weed detection using deep learning - Faiza Khan; Muhammad Naveed Tahir; Muhammad Aqib; Yubin Lan; Noureen Zafar; Shoaib Saleem; Zainab Haroon; Wenjiang Huang (Computers and Electronics in Agriculture, 2026)

Fabrication and In-Vitro Evaluation of Floating Tablets of Levofloxacin Hemihydrate for the Local Treatment of Helicobacter Pylori Infection - Abdullah Khan; Asif Nawaz; Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Haroon Khan; Muhammad Musa Khan; Irum Farooq; Saima Mahmood (Journal of Pharmaceutical Innovation, 2026)

Enhancing skin moisture and anti-aging by DL-α-tocopherol loading sodium alginate-based hydrogel microneedles - Khan Manqoosh Awan; Haojie Yu; Li Wang; Muhammad Haroon; Abdul Basit; Jian Hu; Jingyi Feng; Muhammad Owais Malik; Dileep Ahmad; Saqlain Raza; Hammal Majeed (Drug Delivery and Translational Research, 2026)

New frontiers in beverage fortification: Delivery of functional ingredients via micro- and nanoencapsulation in dairy and non-dairy beverages - Mohammad Rezaul Islam Shishir; Suliman Khan; Naymul Karim; Muhammad Bilal; Sarfaraz Hussain; Md Saifullah; Ahmed K. Rashwan; Haroon Elrasheid Tahir; Isam A. Mohamed Ahmed; Xinhua Zhang; Fujun Li (Food Research International, 2026)

Development of cytarabine-loaded pH-responsive polymeric hydrogel: an in vitro and in vivo evaluation - Shaheer Khalid; Sharjeel Adnan; Asif Mahmood; Rai Muhammad Sarfraz; Hira Ijaz; Muhammad Farooq; Bilal Haroon (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Enhancing the immunogenicity of a recombinant PEDV subunit vaccine: the role of lipoprotein signal peptide - Haroon Afzal; Muhammad Umar; Nguyen-Thanh Hoa; Guan-Ming Ke; Li-Ting Cheng (Archives of Virology, 2026)

Xanthan gum-stabilized cocoa butter emulsion: characterization, molecular interactions, physicochemical stability, and bioaccessibility of α-mangostin - Naymul Karim; Ke Zhang; Mohammad Rezaul Islam Shishir; Mohammad Nasiruddin Rana; Gobinath Marappan; Muhammad Arslan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Isam A. Mohamed Ahmed; Jitbanjong Tangpong; Xiaobo Zou (Food Chemistry, 2026)

Near-infrared, mid-infrared and Raman spectral feature information fusion strategy for multivariate quantitative analysis of polyphenols in Pakistani rice - Muhammad Arslan; Muhammad Zareef; Haroon Elrasheid Tahir; Muhammad Arslan; Allah Rakha; Zou Xiaobo (Food Control, 2026)

Synergistic effect of prednisolone and omega-3 fatty acids revealed through in silico, in vitro, and in vivo approaches against APAP-induced mouse model of acute liver injury - Zainab Rehman; Muhammad Ali; Arifa Mehreen; Ghulam Mustafa; Bushra Akhtar; Ali Sharif; Sehrish Murtaza; Muhammd Haroon Hamed; Amina Sagheer; Mahnoor Yamin (Toxicology and Applied Pharmacology, 2026)

Phenotypic Plasticity of Safflower Genotypes in Response to Contrasting Climatic Conditions - Obaid Afzal; Mukhtar Ahmed; Sahir Hameed Khattak; Muhammad Aqeel Aslam; Saida Komal; Maryam Murtaza; Farrukh Bashir; Aqeel Ahmad; Aliya Mirbaz; Haroon Ur Rasheed; Ghulam Muhammad Ali; Muhammad Usman; et al. (Plant Molecular Biology Reporter, 2025)

Kaempferol suppresses TLR-2 and TLR-4 coactivation by attenuation of LPS/LTA-induced inflammation and cellular stress - Muhammad Haroon; Sun Chul Kang (Molecular Biology Reports, 2025)

A smart olfactory visualization system based on colorimetric sensor array and chemometrics for the identification of rice adulteration - Muhammad Arslan; Muhammad Zareef; Mubrrah Afzal; Haroon Elrasheid Tahir; Jiyong Shi; Arslan Muhammad; Allah Rakha; Zou Xiaobo (Food Chemistry, 2025)

Environmental Concern and Digital Engagement as Drivers of Circular Product Buying Intention in Malaysia: an Integrated S-O-R, TPB, and DOI Perspective - Husam Ahmad Kokash; Mst. Nilufar Ahsan; Muhammad Haroon Hafeez; Amira Naqeeb Khattak; Saif Ahmed; Syed Shah Alam (Circular Economy and Sustainability, 2025)

Corrigendum to ‘Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting’ [Chemosphere 310 (2023) 136835] - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2025)

Lignocellulosic biomass as a renewable resource: Driving second-generation biofuel innovation from agricultural waste - Irum Bukhari; Fazal Haq; Mehwish Kiran; Tariq Aziz; Sahid Mehmood; Muhammad Haroon (Biomass and Bioenergy, 2025)

From metabolic dysregulation to neurodegenerative pathology: the role of hyperglycemia, oxidative stress, and blood-brain barrier breakdown in T2D-driven Alzheimer’s disease - Ahmad Raza; Shafaq Saleem; Samar Imran; Sarah Rahman; Muhammad Haroon; Azeen Razzaq; Ahmad Hussain; Javed Iqbal; Brijesh Sathian (Metabolic Brain Disease, 2025)
Type 2 Diabetes (T2D) and Alzheimer’s Disease (AD) share common risk factors that can be seen through T2D nearly doubling an individual’s likelihood of developing AD. Some AD patients show signs of metabolic dysfunction as well. This review focuses on the potential mechanisms associated with these two diseases, like insulin resistance, inflammation, oxidative damage, mitochondrial injury, and cell death. One of the notable elements in this connection is the “brain insulin resistance,” most frequently named as “type 3 diabetes,” which impairs glucose metabolism and facilitates amyloid beta (Aβ) plaque synthesis while reducing the action of insulin-degrading enzyme (IDE). Moreover, the overactivity of glycogen synthase kinase-3 beta (GSK-3β) also triggers taurine protein pathology. Raised concentrations of glucose in blood can produce advanced glycation end products (AGEs), which further exacerbate neuroinflammation in tandem with the mitigation of neurotoxic Aβ oligomers. Inflammation and subsequent damage to mitochondria lead to the dissolution of synapses. Current vascular insults include the breakdown of the blood-brain barrier (BBB) and decreased brain perfusion, along with other contributory factors to conditions conducive to neurotoxicity. Recently, novel therapies are emerging, including GLP-1 agonists, intranasal insulin, and mitochondrial antioxidants, that show surprising results for treating both conditions, but on the contrary, bioavailability and the timing of interventions remain a big challenge in the management of these diseases. Eventually, further research should center on understanding the mechanisms of integration along with the development of molecular biology, neuroimaging, and outcome-driven treatment strategies. Comprehensive strategies that exist between T2D-AD for integration and preservation of brain and metabolic health are addressed in this review. Graphical abstract

L-Shaped Association Between Dietary Copper Intake and Chronic Obstructive Pulmonary Disease Among American Adults: Findings From the National Health and Nutrition Examination Survey 1999–2018 - Chengfeng Fu; Junwei Shi; Muhammad Haroon; Jing Luo; Ying Hu; Depeng Jiang (Journal of the Academy of Nutrition and Dietetics, 2025)

Sustainable water management practice in South Asian Countries: The importance of water resources, temperature, and bioenergy on ecological footprint - Muhammad Haroon Shah; Syed Tauseef Hassan; Irfan Ullah; Yaoyao Wang; Ashfaq Ahmad Shah (Gondwana Research, 2025)

Formulation and Characterization of Isavuconazole-Loaded Chitosan/Sodium Alginate Nanoparticles for Dermal Delivery: in Vitro and in Vivo Evaluation for Enhanced Antifungal Therapy - Shahzad Khan; Asif Nawaz; Muhammad Khursheed Alam Shah; Muhammad Shahid Latif; Muhammad Haroon; Abdullah Khan; Tarek Mohamed Ali Elsayed (Journal of Pharmaceutical Innovation, 2025)

Driving innovation in fast-food industry: integrating green HRM, green empowerment, and green CSR - Jamshed Khalid; Mi Chuanmin; Muhammad Umair Ashraf; Muhammad Haroon Rasheed; Muhammad Shahid Rasheed (Environment, Development and Sustainability, 2025)

Health risks associated with occupational contaminants of heavy metals across different professions - Sosan Andleeb Khan; Syed Muhammad Nurulain; Baseet Haroon Khan; Aneela Shoukat; Sajid Mehmood; Rabeet Haroon Khan; Rashid Nazir Qureshi; Amina Zafar; Ammara Younas; Syed Tahir Abbas Shah (Environmental Geochemistry and Health, 2025)

Machine learning-based detection and quantification of red blood cells in Cholistani cattle: A pilot study - Sami Ul Rehman; Sania Fayyaz; Muhammad Usman; Mehreen Saleem; Umer Farooq; Asjad Amin; Mushtaq Hussain Lashari; Musadiq Idris; Haroon Rashid; Maryam Chaudhary (Research in Veterinary Science, 2025)

The interrelation among environmental quality, public accounts, and macroeconomic fundamentals: An analysis of OECD countries using machine learning techniques - Cosimo Magazzino; Muhammad Haroon (Environmental Development, 2025)

Effect of Diagenetic Processes and Depositional Facies on Reservoir Quality of the Eocene Carbonate Sequence (Sakesar Limestone) in the Central Salt Range, Pakistan - Naveed Rehman; Shu Jiang; Syed Haroon Ali; Asim Falak Naz; Muhammad Tariq (Journal of Earth Science, 2025)

Rhizospheric bacterial strain Pseudomonas putida and fungal strain Penicillium chrysogenum alleviate Fusarium wilt of tomato by improving key growth attributes - Hassaan Ateeb Ahmad; LNU Farhana; Urooj Haroon; Hira Saleem; Maryam Anar; Mahnoor Akbar; Kanwal Abbasi; Abdul Rehman; Mohammad Sameer Zubair; Asif Kamal; Hassan Javed Chaudhary; Rattandeep Singh; et al. (European Journal of Plant Pathology, 2025)

Spatio‐Temporal Dynamics of Vegetation and Land Surface Temperature in Saudi Arabia: Impacts of Climate Change on Agricultural Sites From 2010 to 2023 - Mazen E. Assiri; Md. Arfan Ali; Lama Alamri; Muhammad Haroon Siddiqui; Ayman S. Ghulam; Shamsuddin Shahid (International Journal of Climatology, 2025)
Saudi Arabia has one of the greatest water shortages and the least vegetation in the world, which is potentially exacerbating the issue of environmental impacts. Therefore, it is crucial to understand the interaction between climate change, vegetation dynamics and land surface temperature (LST). The present study investigates the spatio‐temporal distributions, variations, change detection and trends of vegetation dynamics and surface temperature over eight agricultural sites in Saudi Arabia using the Normalised Difference Vegetation Index (NDVI) and LST from Landsat 7 (Enhance Thematic Mapper Plus: ETM + ) and Landsat 8 (operational land imager: OLI) measurements for the period 2010–2023. The study also examined the relationship between NDVI, LST and climate variables such as air temperature, rainfall, relative humidity and soil moisture. Results showed that an NDVI > 0.20 represents vegetation in Saudi Arabia. Higher values of NDVI were found in Baysh, Jazan province, compared to other agricultural sites. Significant annual and seasonal variations in NDVI were also observed across eight major agricultural sites in Saudi Arabia, attributable to the region's varying climate conditions. Vegetation expansion in 2023 exceeded that in 2014 in Buraydah (304.34 km 2 ), Tabarjal (63.81 km 2 ), Hail (33.20 km 2 ), Al Qirw (22.53 km 2 ) and Baysh (3.07 km 2 ), while reductions were noted in Wadi Al Dawasir (274.58 km 2 ), Tabuk (88.56 km 2 ) and Al Ahsa (27.30 km 2 ). The LST over soil and vegetated surfaces showed that vegetation notably reduced LST at Hail (3.14°C), Al Ahsa and Wadi Al Dawasir (5.43°C), Buraydah (4.53°C), Baysh (2.71°C), Al Qirw (5.17°C), Tabuk (6.24°C) and Tabarjal (3.13°C). The study found that NDVI, LST and climate variables are positively and negatively correlated, which indicates a significant impact of climate change on vegetation patterns. The findings of this study are highly relevant for informing agricultural and environmental policy development in Saudi Arabia, with a focus on enhancing vegetation cover, mitigating the impacts of rising temperatures and advancing sustainable agricultural practices to address the challenges posed by climate change.

Greening the mines: Managing efficiency, environmental impact, and ecology in Chinese mining regions - Cosimo Magazzino; Muhammad Haroon; Xian Zeo (Resources Policy, 2025)

Assessing the dual impact of gold mining on local communities: Socio-economic benefits and environmental challenges - Muhammad Haroon; Muhammad Hayyat (Resources Policy, 2025)

Two years monitoring and optimization of a large-scale constructed wetland in the Red Sea designed for 80,000 inhabitants - Muhammad Ishtiaq; Muhammad Akram; Shezhi Tao; Hicham Belmaati; Muhammad Haroon Siyech; Wolfarm Sievert; Alexandros Stefanakis (Journal of Cleaner Production, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Enhancing wheat resilience: biotechnological advances in combating heat stress and environmental challenges - Muhammad Arif; Muhammad Haroon; Ayesha Fazal Nawaz; Hina Abbas; Ruhong Xu; Luhua Li (Plant Molecular Biology, 2025)

Impact of emerging technologies on corporate social responsibility in mining industry - Muhammad Haroon; Mirzat Ullah; Zhanqiang Li; Shuo Zhu; Judong Wang; Chu-Pin (Eugune) Hsueh (Resources Policy, 2025)

Impact of urea-molasses treated wheat straw levels in total mixed rations on growth and nutrient digestibility in Azikheli buffalo calves - Haroon Ur Rashid; Taimoor Khan; Anwar Ali Turi; Muhammad Abbas; Kalim Ullah; Isa Fusaro; Giovanni Buonaiuto; Damiano Cavallini (Tropical Animal Health and Production, 2025)
This study investigates the impact of urea molasses-treated wheat straw on growth performance and nutrient digestibility in Azikheli buffalo male calves. A longitudinal experiment was conducted on sixteen calves, randomly assigned to four experimental dietary treatments ( n = 4 per group). The experimental diets included a control group (U0) with untreated wheat straw and three groups where urea molasses-treated wheat straw replaced 33% (U33), 66% (U66), or 100% (U100) of the straw in the total mixed ration. Results indicated that increasing the proportion of urea-treated wheat straw from 0 to 100% led to significant improvements in dry matter intake (from 2931 to 4034 g/day) and organic matter intake (from 2596 to 3623 g/day). Digestibility of dry matter, organic matter, crude protein, and crude fiber also followed an increasing trend, reaching 77.42%, 81.21%, 87.10%, and 60.22%, respectively, at the highest urea-treated wheat straw level. Furthermore, weight gain was significantly greater in calves fed 100% urea-treated wheat straw, followed by those in the U66, U33, and U0 groups. Feed conversion efficiency improved substantially in the U100 and U66 groups than U33 and U0. These findings suggest that incorporating higher levels of UMTWS in total mixed rations enhances nutrient digestibility, promoting superior growth performance and feed efficiency in Azikheli buffalo calves.

Systematic review of the digestive fate of rice phenolic compounds: Insights into bioavailability, influencing factors, encapsulation strategies, and health implications - Halah Aalim; Mohammad Rezaul Islam Shishir; Nermeen Yosri; Muhammad Arslan; Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Naymul Karim; Xiaodong Zhai; Zhihua Li; Chenguang Zhou; Xiaobo Zou (Trends in Food Science & Technology, 2025)

Modified approach to estimate effective porosity using density and neutron logging data in conventional and unconventional reservoirs - Muhammad Abid; Jing Ba; Uti Ikitsombika Markus; Zeeshan Tariq; Syed Haroon Ali (Journal of Applied Geophysics, 2025)

Development and In-Vitro Tuning of Piperine Containing Solid Lipid Microparticles for the Treatment of Rheumatoid Arthritis - Muneeba Aziz; Sajid Bashir; Rai Muhammad Sarfraz; Hira Ijaz; Asif Mahmood; Zulcaif; Bilal Haroon; Milad A. Mezher; Mohamed M. Salem; Sami Al Zahrani; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

A comprehensive review on advanced trends in treatment technologies for removal of Bisphenol A from aquatic media - Sangeen Waleed; Muhammad Haroon; Naeem Ullah; Mustafa Tuzen; Imran Khan Rind; Ahmet Sarı (Environmental Monitoring and Assessment, 2024)

Spatial distribution of groundwater quality and risk indices evaluation via consumption - Said Muhammad; Rizwan Ullah; Sehrish Amin; Haseeb Haroon; Ashfaq Ahmad (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Characterization and identification of the key volatile and non-volatile substances of Vangueria madagascariensis J.F. Gmel fruits (Kirkir) and exploration of their binding interactions with olfactory and taste receptors using computational chemistry methodology - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Mohammad Rezaul Islam Shishir; Li Zhihua; Suliman Khan; Abdalbasit Adam Mariod; Hamza A.M. Abaker; Howida Elkheir Ibrahim; Hesham R. El-Seedi; Zou Xiaobo (Food Chemistry, 2024)

The association of ABCB1 gene polymorphism with clinical response to carbamazepine monotherapy in patients with epilepsy - Haroon Ur Rashid; Shakir Ullah; Daniel F. Carr; Muhammad Ijaz Khan Khattak; Muhammad Imran Asad; Mujeeb Ur Rehman; Muhammad Khalid Tipu (Molecular Biology Reports, 2024)

Assessment of Machine Learning Algorithms for Land Cover Classification in a Complex Mountainous Landscape - Gomal Amin; Iqra Imtiaz; Ehsan Haroon; Najum us Saqib; Muhammad Imran Shahzad; Majid Nazeer (Journal of Geovisualization and Spatial Analysis, 2024)
Mapping land cover (LC) in mountainous regions, such as the Gilgit-Baltistan (GB) area of Pakistan, presents significant challenges due to complex terrain, limited data availability, and accessibility constraints. This study addresses these challenges by developing a robust, data-driven approach to classify LC using high-resolution Sentinel-2 (S-2) satellite imagery from 2019 within Google Earth Engine (GEE). The research evaluated the performance of various machine learning (ML) algorithms, including classification and regression tree (CART), maximum entropy (gmoMaxEnt), minimum distance (minDistance), support vector machine (SVM), and random forest (RF), without extensive hyperparameter tuning. Additionally, ten different scenarios based on various band combinations of S-2 data were used as input for running the ML models. The LC classification was performed using 2759 sample points, with 70% for training and 30% for validation. The results indicate that the RF algorithm outperformed all other classifiers under scenario S1 (using 10 bands), achieving an overall accuracy (OA) of 0.79 and a kappa coefficient of 0.76. The final RF-based LC mapping shows the following percentage distribution: barren land (46.7%), snow cover (22.9%), glacier (7.9%), grasses (7.2%), water (4.7%), wetland (2.9%), built-up (2.7%), agriculture (1.9%), and forest (1.2%). It is suggested that the best identified RF classifier within the GEE environment should be used for advanced multi-source data image classification with hyperparameter tuning to increase OA. Additionally, it is suggested to build the capacity of various stakeholders in GB for better monitoring of LC changes and resource management using geospatial big data.

De novo assembly of sialotranscriptome of Hyalomma anatolicum and insights into expression dynamics in response to Theileria annulata infection - Adeel Mumtaz Abbasi; Shiza Nasir; Amna Arshad Bajwa; Haroon Akbar; Sara Artigas-Jerónimo; Clara Muñoz-Hernández; Marta Sánchez-Sánchez; Alberto Moraga-Fernández; Isabel G. Fernández de Mera; José de la Fuente; Muhammad Imran Rashid (Experimental and Applied Acarology, 2024)

Deposition and diagenesis of the Triassic-Jurassic limestone successions of the northwestern passive margin of the Indian plate, Sulaiman Fold-Thrust Belt, Pakistan - Razzaq Abdul Manan; Akhtar Muhammad Kassi; Henrik Friis; Aimal Khan Kasi; Syed Haroon Ali; Mohammad Ahmed Farooqui; Muhammad Ishaq Kakar (Carbonates and Evaporites, 2024)

Recent advances in delivering mangosteen-based phytochemicals using promising micro/nanocarriers: Formulation, outcomes, and perspectives - Naymul Karim; Mohammad Rezaul Islam Shishir; Gobinath Marappan; Suliman Khan; Sulafa B.H. Hashim; Halah Aalim; Muhammad Arslan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Md. Atiar Rahman; Jitbanjong Tangpong; et al. (Trends in Food Science & Technology, 2024)

Remote Sensing Assessment of Water Resources, Vegetation, and Land Surface Temperature in Eastern Saudi Arabia: Identification, Variability, and Trends - Mazen E. Assiri; Md Arfan Ali; Muhammad Haroon Siddiqui; Albandari AlZahrani; Lama Alamri; Abdullah Masoud Alqahtani; Ayman S. Ghulam (Remote Sensing Applications: Society and Environment, 2024)

Micro and nano-encapsulated natural products in yogurt: An emerging trend to achieve multifunctional benefits in product quality and human health. - Mohammad Rezaul Islam Shishir; Md Saifullah; Sulafa B.H. Hashim; Halah Aalim; Muhammad Bilal; Suliman Khan; Gobinath Marappan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Muhammad Arslan; Farah Saleena Taip; et al. (Food Hydrocolloids, 2024)

Potato Chip Varietal Analysis: a Comparative Evaluation Based on Potato Cultivars - Talha Khalil; Muhammad Haroon; Sumaira Miskeen; Shehla Sammi; Muhammad Jahangir; Sara Najeeb; Kainat Nisar; Arsalan Khan; Muhammad Liaquat; Imran Khan; Jae-Won Ha (Potato Research, 2024)

Estimation of transport CO2 emissions using machine learning algorithm - Shengwei Li; Zeping Tong; Muhammad Haroon (Transportation Research Part D: Transport and Environment, 2024)

Bacteria-Based MnO Nanoparticles Alleviate Lead Toxicity in Tomato Seedling Through Improving Growth Attributes and Enhanced Gene Expression of Candidate Genes - Maryam Anar; Urooj Haroon; Asif Kamal; Kinza Tahir; Mahnoor Akbar; Farhana; Hira Saleem; Abdul Rehman; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Journal of Plant Growth Regulation, 2024)

Assessment of textile effluent treatment by immobilized Trametes pubescens MB 89 for plant growth promotion - Uroosa Ejaz; Saima Zakir; Zainul Abideen; Bushra Fahim; Waniya Shaikh; Faryal Shakil; Fizza Haroon Mirza; Syed Wasi Haider; Adnan Khan; Muhammad Sohail (Environmental Science and Pollution Research, 2024)

Assessing the health risks of heavy metals and seasonal minerals fluctuations in Camellia sinensis cultivars during their growth seasons - Fawad Zaman; Wajid Ali Khattak; Muhammad Ihtisham; Muhammad Ilyas; Ahmad Ali; Abbas Ali; Haroon Khan; Khalid Ali Khan; Dejiang Ni; Hua Zhao; Fu-Sheng Chen (Food and Chemical Toxicology, 2024)

How causality impacts the renewable energy, carbon emissions, and economic growth nexus in the South Caucasus Countries? - Azer Dilanchiev; Muhammad Umair; Muhammad Haroon (Environmental Science and Pollution Research, 2024)

Brown macro-seaweeds derived agro-biostimulant for Zea mays farming in saline conditions: Growth enhancement and optimum biochemical and ion feedback - Sadaf Gul; Muhammad Farrakh Nawaz; Muhammad Talha Bin Yousaf; Muhammad Haroon U Rashid; Muhammad Yousuf Adnan; Shamama Tausif; Arooj Javed; Zainul Abideen; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Bacillus safensis filtrate-based ZnO nanoparticles control black heart rot disease of apricot fruits by maintaining its soluble sugars and carotenoids - Farhana; Abu Bakr Umer Farooq; Urooj Haroon; Hira Saleem; Mahnoor Akbar; Maryam Anar; Muhammad Nawaz; Hassaan Ateeb Ahmad; Junaid Ahmed; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (World Journal of Microbiology and Biotechnology, 2024)

Exercise Improves Cerebral Blood Flow and Functional Outcomes in an Experimental Mouse Model of Vascular Cognitive Impairment and Dementia (VCID) - Mohammad Badruzzaman Khan; Haroon Alam; Shahneela Siddiqui; Muhammad Fasih Shaikh; Abhinav Sharma; Amna Rehman; Babak Baban; Ali S. Arbab; David C. Hess (Translational Stroke Research, 2024)

How do corporate social responsibility initiatives enhance sustainability performance? Evidence from tobacco firms - Muhammad Haroon Shoukat; Kareem M. Selem; Dongmei Cao (Environment, Development and Sustainability, 2024)

Spherical Fe2O3 nanoparticles inhibit the production of aflatoxins (B1 and B2) and regulate total soluble solids and titratable acidity of peach fruit - Mahnoor Akbar; Naeem Ali; Muhammad Imran; Arshad Hussain; Syed Waqas Hassan; Urooj Haroon; Asif Kamal; Farhana; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (International Journal of Food Microbiology, 2024)

HPLC-DAD, GC–MS, UHPLC-Q-TOF/MS2, ICP-MS and FT-NIR combined with the chemometrics explain seasonal variation in Cassia senna L. leaves from the coast of Red Sea in Sudan - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Huang Xiaowei; Li Zhihua; Abdalbasit Adam Mariod; Isameldeen I.H. Abdalla; Hesham R. El-Seedi; Ahmed Abdel Aziz Ahmed; Zou Xiaobo (South African Journal of Botany, 2023)

Impact of different proportions of sweet potato (Ipomoea batatas L.) flour on physical, chemical and sensory parameters of straight grade flour-based cake rusk - Hafiza Saher Rafique; Ashiq Hussain; Muhammad Nadeem; Abdul Rehman; Tahira Siddique; Ayesha Najam; Haseeb Haroon; Muhammad Rehan Arif; Shazia Yaqub; Haya Fatima; Salah Laaraj (Food and Humanity, 2023)

Spatiotemporal variation in the vegetation cover of Peshawar Basin in response to climate change - Ishaq Ali Shah; Zahir Muhammad; Haroon Khan; Rehman Ullah; Atta-ur Rahman (Environmental Monitoring and Assessment, 2023)

Towards achieving university sustainability! Linking social responsibility with knowledge sharing in Saudi universities - Afroze Nazneen; Islam Elgammal; Zubair Rashid Khan; Muhammad Haroon Shoukat; Ali Elsayed Shehata; Kareem M. Selem (Journal of Cleaner Production, 2023)

Sustainable remediation of dye-contaminated wastewater using novel cross-linked Hex-CCP-co-PPT microspheres - Sahid Mehmood; Fazal Haq; Mehwish Kiran; Ibrahim A. Shaaban; Mohammed A. Assiri; Muhammad Haroon; Muhammad Yasin; Arshad Farid; Alam Nawaz; Majid Majeed Akbar; Zeinhom M. El-Bahy (Chemosphere, 2023)

Pharmacological and toxicological evaluation of methyl 4-hydroxy-2H-1,2-benzothiazine-3-carboxylate 1,1-dioxoide against haloperidol induced Parkinson like symptoms in animal model: In-vitro and in-vivo studies - Liaqat Hussain; Ina Masood; Matloob Ahmad; Muhammad Yasir Ali; Uzma Saleem; Musaddique Hussain; Syed Haroon Khalid; Zunera Chauhdary (Toxicology and Applied Pharmacology, 2023)

Guiding the optimization of membraneless microfluidic fuel cells via explainable artificial intelligence: Comparative analyses of multiple machine learning models and investigation of key operating parameters - Dang Dinh Nguyen; Muhammad Tanveer; Hang-Nga Mai; Thinh Quy Duc Pham; Haroon Khan; Cheol Woo Park; Gyu Man Kim (Fuel, 2023)

Administration of α-lipoic acid and silymarin attenuates aggression by modulating endocrine, oxidative stress and inflammatory pathways in mice - Adnan Karim; Fareeha Anwar; Uzma Saleem; Saniya Fatima; Tariq Ismail; Ahmad J. Obaidullah; Rana O. Khayat; Moneerah J. Alqahtani; Ifat Alsharif; Haroon Khan; Celia Vargas-De-La-Cruz; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Assessment of landcover impacts on the groundwater quality using hydrogeochemical and geospatial techniques - Javed Iqbal; Gomal Amin; Chunli Su; Ehsan Haroon; Muhammad Yousuf Jat Baloch (Environmental Science and Pollution Research, 2023)

Progress in genome-wide identification of RBPs and their role in mitigating stresses, and growth in plants - Muhammad Haroon; Hala Tariq; Rabail Afzal; Muhammad Anas; Shanza Nasar; Neha Kainat; Sajid Fiaz; Uswa Irfan; Fahad Idrees; Muhammad Mubashar Zafar (South African Journal of Botany, 2023)

Ginsenosides in cancer: Targeting cell cycle arrest and apoptosis - Muhammad Ajmal Shah; Syed Muhammad Abuzar; Kainat Ilyas; Irtaza Qadees; Momna Bilal; Rimsha Yousaf; Roaa Mohammed Tahir Kassim; Azhar Rasul; Uzma Saleem; Maria Silvana Alves; Haroon Khan; Renald Blundell; et al. (Chemico-Biological Interactions, 2023)

Effect of green Fe2O3 nanoparticles in controlling Fusarium fruit rot disease of loquat in Pakistan - Faryal Niazi; Musrat Ali; Urooj Haroon; Farhana; Asif Kamal; Taskeen Rashid; Fareeha Anwar; Rabia Nawab; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Brazilian Journal of Microbiology, 2023)

The impact of green economic recovery on economic growth and ecological footprint: A case study in developing countries of Asia - Shengming Chen; Fushuai Wang; Muhammad Haroon (Resources Policy, 2023)

Financing efficiency in natural resource markets mobilizing private and public capital for a green recovery - Juan Yan; Muhammad Haroon (Resources Policy, 2023)

Exploring the relationship between global economic policy and volatility of crude futures: A two-factor GARCH-MIDAS analysis - Ying Fang; Ying Fan; Muhammad Haroon; Azer Dilanchiev (Resources Policy, 2023)

Modulating hydrophilic properties of β-cyclodextrin/carboxymethyl cellulose colloid particles to stabilize Pickering emulsions for food 3D printing - Ziang Guo; Zhihua Li; Shaoyi Cen; Nini Liang; Arslan Muhammad; Haroon Elrasheid Tahir; Jiyong Shi; Xiaowei Huang; Xiaobo Zou (Carbohydrate Polymers, 2023)

Anti-inflammatory mechanisms of eucalyptol rich Eucalyptus globulus essential oil alone and in combination with flurbiprofen - Bushra Arooj; Sajid Asghar; Mohammad Saleem; Syed Haroon Khalid; Muhammad Asif; Tahir Chohan; Ikram Ullah Khan; Hafiz Muhammad Zubair; Hafiza Sidra Yaseen (Inflammopharmacology, 2023)

Use of remote sensing-based pressure-state-response framework for the spatial ecosystem health assessment in Langfang, China - Anam Ashraf; Muhammad Athar Haroon; Shakeel Ahmad; Ahmed Samir Abowarda; Chunyue Wei; Xuehua Liu (Environmental Science and Pollution Research, 2023)

Anticancer effects of phytol against Sarcoma (S-180) and Human Leukemic (HL-60) cancer cells - Marcus Vinícius Oliveira Barros de Alencar; Muhammad Torequl Islam; Ana Maria Oliveira Ferreira da Mata; Antonielly Campinho dos Reis; Rosália Maria Torres de Lima; José Roberto de Oliveira Ferreira; João Marcelo de Castro e Sousa; Paulo Michel Pinheiro Ferreira; Ana Amélia de Carvalho Melo-Cavalcante; Abdur Rauf; Hassan A. Hemeg; Khalaf F. Alsharif; et al. (Environmental Science and Pollution Research, 2023)

Access to sustainable healthcare infrastructure: a review of industrial emissions, coal fires, and particulate matter - Muhammad Imran; Shiraz Khan; Abdelmohsen A. Nassani; Mohamed Haffar; Haroon ur Rashid Khan; Khalid Zaman (Environmental Science and Pollution Research, 2023)

Classification of Black Mahlab seeds (Monechma ciliatum) using GC–MS and FT-NIR and simultaneous prediction of their major volatile compounds using chemometrics - Haroon Elrasheid Tahir; Abdalbasit Adam Mariod; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Huang Xiaowei; Li Zhihua; Isameldeen I.H. Abdalla; Zou Xiaobo (Food Chemistry, 2023)

Preliminary Geoheritage Assessment of The Gharam Chashma Granitic Batholith (GCGB), Southern Margin of Asian Plate, NW Pakistan: Multiple Constraints from Field Evidence, Petrology, and Physicomechanical Properties - Abbas Ali Naseem; Muhammad Naveed Anjum; Muhammad Yaseen; Muhammad Ali; Waqar Inam; Syed Haroon Ali; Jawad Ahmad; Anees Ahmad Bangash (Geoheritage, 2023)

Correction to: Morphology of testis, sperm, and spermatheca in two capable hybridized termite species indicates no interspecific reproductive isolation - Zahid Khan; Mian Sayed Khan; Suleman; Nehaz Muhammad; Haroon; Xiao-Hong Su; Lian-Xi Xing (International Journal of Tropical Insect Science, 2023)

Silver-loaded silica/H-ZSM-5 nanocomposite as a sensitive SERS substrate for the detection of sulfur-containing compounds in diesel fuel - Sathiyamoorthy Murugesan; Muhammad Haroon; Tawfik A. Saleh; Abdulaziz A. Al-Saadi (Fuel, 2023)

Biofilm formation and flocculation potential analysis of halotolerant Bacillus tequilensis and its inoculation in soil to mitigate salinity stress of chickpea - Urooj Haroon; Muhammad Farooq Hussain Munis; Fiza Liaquat; Maria Khizar; Minhas Elahi; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2023)

Antidepressant activity of phytochemicals of Mangifera indica seeds assisted by integrated computational analysis - Uzma Saleem; Shafa Iman; Bashir Ahmad; Muhammad Ajmal Shah; Shabana Bibi; Mohammed Alqarni; Muhammad Saad Khan; Ghulam Mujtaba Shah; Haroon Khan; Reem Hasaballah Alhasani; Norah A. Althobaiti; Aishah E. Albalawi (Metabolic Brain Disease, 2023)

Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Molecular epidemiology and characterization of Babesia bovis in cattle of Khyber Pakhtunkhwa province, Pakistan - Muhammad Shoaib; Muhammad Imran Rashid; Haroon Akbar; Ali Ahmad Sheikh; Shahid Hussain Farooqi; Amel Ayari-Akkari; Habab M. Yassin; Rajwali Khan (Tropical Animal Health and Production, 2022)

Dominant complementation of biological pathways in maize hybrid lines is associated with heterosis - Tao Zhou; Rabail Afzal; Muhammad Haroon; Yuting Ma; Hongwei Zhang; Lin Li (Planta, 2022)

Exogenous Selenium as a Potent Modulator of Antioxidants, Osmo-protectants, Lipid Peroxidation, and Wheat Grain Yield Under Terminal Heat Stress - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Haroon Zaman Khan (Journal of Soil Science and Plant Nutrition, 2022)

Sedimentological and diagenetic analysis of Early Eocene Margalla Hill Limestone, Shahdara area, Islamabad, Pakistan: implications for reservoir potential - Haroon Aziz; Jabir Hussain; Muhammad Tariq; Muhsan Ehsan; Salman Khurshid; Saleem Khan; Waleed Anwar (Carbonates and Evaporites, 2022)

Correction to: Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

Halotolerant Plant Growth-Promoting Rhizobacteria Induce Salinity Tolerance in Wheat by Enhancing the Expression of SOS Genes - Urooj Haroon; Maria Khizar; Fiza Liaquat; Musrat Ali; Mahnoor Akbar; Kinza Tahir; Syeda Saira Batool; Asif Kamal; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Journal of Plant Growth Regulation, 2022)

Morphology of testis, sperm, and spermatheca in two capable hybridized termite species indicates no interspecific reproductive isolation - Zahid Khan; Mian Sayed Khan; Suleman; Nehaz Muhammad; Haroon; Xiao-Hong Su; Lian-Xi Xing (International Journal of Tropical Insect Science, 2022)

Characterization of functional genes GS3 and GW2 and their effect on the grain size of various landraces of rice (Oryza sativa) - Haroon Rasheed; Sajid Fiaz; Muhammad Abid Khan; Sultan Mehmood; Faizan Ullah; Sumbul Saeed; Shahid Ullah Khan; Tabassam Yaseen; Reem M. Hussain; Abdul Qayyum (Molecular Biology Reports, 2022)

Therapeutic potential of herbal medicine for the management of hyperlipidemia: latest updates - Abdur Rauf; Muhammad Akram; Hina Anwar; Muhammad Daniyal; Naveed Munir; Sami Bawazeer; Saud Bawazeer; Maksim Rebezov; Abdelhakim Bouyahya; Mohammad Ali Shariati; Muthu Thiruvengadam; Orynzhamal Sarsembenova; et al. (Environmental Science and Pollution Research, 2022)

A modified approach to quantify aquifer vulnerability to pollution towards sustainable groundwater management in Irrigated Indus Basin - Muhammad Umar; Shahbaz Nasir Khan; Arfan Arshad; Rana Ammar Aslam; Hafiz Muhammad Safdar Khan; Haroon Rashid; Quoc Bao Pham; Abdul Nasir; Rabeea Noor; Khaled Mohamed Khedher; Duong Tran Anh (Environmental Science and Pollution Research, 2022)

Antimicrobial Resistance of Shigella flexneri in Pakistani Pediatric Population Reveals an Increased Trend of Third-Generation Cephalosporin Resistance - Iqbal Nisa; Mohammad Haroon; Arnold Driessen; Jeroen Nijland; Hazir Rahman; Nusrat Yasin; Mubashir Hussain; Taj Ali Khan; Amjad Ali; Saeed Ahmad Khan; Muhammad Qasim (Current Microbiology, 2022)

Preparation and Quality Attributes of Egg-reduced Pound Cake Incorporating Grass Carp ( Ctenopharyngodonidella ) Protein Concentrate - Sohail Khan; Haroon Shah; Sajid Kamal; Abdur Rehman; Qayyum Shehzad; Umer Karamat; Aiman Karim; Mudassar Hussain; Muhammad Muneeb; Wenshui Xia (Journal of Aquatic Food Product Technology, 2022)

Spatial distribution of carbon dynamics and nutrient enrichment capacity in different layers and tree tissues of Castanopsis eyeri natural forest ecosystem - Taimoor Hassan Farooq; Xen Xincheng; Awais Shakoor; Muhammad Haroon U. Rashid; Muhammad Farhan Bashir; Muhammad Farrakh Nawaz; Uttam Kumar; Sher Muhammad Shahzad; Wende Yan (Environmental Science and Pollution Research, 2022)

Gibberellic acid and urease inhibitor optimize nitrogen uptake and yield of maize at varying nitrogen levels under changing climate - Ikram Ullah; Khadim Dawar; Muhammad Tariq; Muhammad Sharif; Shah Fahad; Muhammad Adnan; Haroon Ilahi; Taufiq Nawaz; Mukhtar Alam; Aman Ullah; Muhammad Arif (Environmental Science and Pollution Research, 2022)

Annual Growth Progression, Nutrient Transformation, and Carbon Storage in Tissues of Cunninghamia lanceolata Monoculture in Relation to Soil Quality Indicators Influenced by Intraspecific Competition Intensity - Taimoor Hassan Farooq; Awais Shakoor; Muhammad Haroon U. Rashid; Saiyang Zhang; Pengfei Wu; Wende Yan (Journal of Soil Science and Plant Nutrition, 2021)

Tick-borne Diseases in Sheep and Goats in Pakistan: A Systematic Review and Meta-analysis - Aqsa Mushtaq; Tehniat Shoukat; Tanzila Mumtaz; Muhammad Qasim; Kiran Ajmal; Nayab Fatima; Aisha Khan; Misbah Kouser; Nazeer Hussain; Sadia Selim Khan; Mohammed Sohail Afzal; Sami Simsek; et al. (Acta Parasitologica, 2021)

Convective available potential energy (CAPE) in Pakistan and its association with precipitation and temperature - Sameen Malik; Rehan Ahmed; Muhammad Latif; Muhammad Azam; Ehsan Haroon; Muhammad Bilal Iqbal (Theoretical and Applied Climatology, 2021)

Climatological and social fallacies about COVID-19 pandemic - Ambar Farooq; Uttam Kumar; Junaite Bin Gais Uddin; Muhammad Haroon U. Rashid; Matoor Mohsin Gilani; Taimoor Hassan Farooq; Awais Shakoor; Matloob Ahmad (Environmental Sustainability, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Optimization, in vitro release and toxicity evaluation of novel pH sensitive itaconic acid-g-poly(acrylamide)/sterculia gum semi-interpenetrating networks - Fauzia Rehman; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Akhtar Rasul; Huma Mahmood; Abid Mehmood Yousaf; Yasser Shahzad; Muhammad Mudassar; Noor Ul Amin Mohsin (DARU Journal of Pharmaceutical Sciences, 2021)

Biochemically Triggered Heat and Drought Stress Tolerance in Rice by Proline Application - Sajid Hanif; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Irshad; Abdul Shakoor; Muhammad Ashfaq Wahid; Haroon Zaman Khan (Journal of Plant Growth Regulation, 2021)

Managing organic carbon of sandy clay loam soil with organic amendments to promote particle aggregation - Haroon Shahzad; Muhammad Iqbal; Noman Latif; Muhammad Arshad Khan; Qudrat Ullah Khan (Arabian Journal of Geosciences, 2021)

Foliar Potassium-Induced Regulations in Glycine Betaine and Malondialdehyde Were Associated with Grain Yield of Heat-Stressed Bread Wheat (Triticum aestivum L.) - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Haroon Zaman Khan; Abdul Shakoor (Journal of Soil Science and Plant Nutrition, 2020)

Calcium-mediated adaptive responses to low phosphorus stress in Chinese fir - Muhammad Haroon U. Rashid; Mulualem Tigabu; Haifeng Chen; Taimoor Hassan Farooq; Xiangqing Ma; Pengfei Wu (Trees, 2020)

Transcriptome analysis of heat stress response genes in potato leaves - Ruimin Tang; Sanjay K. Gupta; Suyan Niu; Xiu-Qing Li; Qing Yang; Guanshui Chen; Wenjiao Zhu; Muhammad Haroon (Molecular Biology Reports, 2020)

Molecular epidemiology of Shigella flexneri isolated from pediatrics in a diarrhea-endemic area of Khyber Pakhtunkhwa, Pakistan - Iqbal Nisa; Muhammad Qasim; Arnold Driessen; Jeroen Nijland; Fazli Bari; Mohammad Haroon; Hazir Rahman; Nusrat Yasin; Taj Ali Khan; Mubbashir Hussain; Waheed Ullah (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Type 1 Fimbriae and Motility Play a Pivotal Role During Interactions of Salmonella typhimurium with Acanthamoeba castellanii (T4 Genotype) - Talha Mannan; Muhammad Wasim Rafique; Muhammad Haroon Bhatti; Abdul Matin; Irfan Ahmad (Current Microbiology, 2020)

Coagulation- and Adsorption-Based Environmental Impact Assessment and Textile Effluent Treatment - Muhammad Aleem; Jiashun Cao; Chao Li; Haroon Rashid; Yang Wu; Muhammad Imran Nawaz; Muhammad Abbas; Muhammad Waqar Akram (Water, Air, & Soil Pollution, 2020)

Adaptations in Imperata cylindrica (L.) Raeusch. and Cenchrus ciliaris L. for altitude tolerance - Khawaja Shafique Ahmad; Ambreen Wazarat; Ansar Mehmood; Muhammad Sajid Aqeel Ahmad; Majid Mahmood Tahir; Fahim Nawaz; Haroon Ahmed; Mohsin Zafar; Aneela Ulfat (Biologia, 2020)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

Retrospective Study of Cystic Echinococcosis (CE) Based on Hospital Record from Five Major Metropolitan Cities of Pakistan - Hira Muqaddas; Muhammad Arshad; Haroon Ahmed; Naunain Mehmood; Aisha Khan; Sami Simsek (Acta Parasitologica, 2019)

Relating iron, zinc, and iodine concentrations of crops to the selected soil properties under field conditions - Bushra Haroon; Sumiya Khan; An Ping; Zahid Hussain; Muhammad Irshad (Arabian Journal of Geosciences, 2019)

Fractionation of heavy metals in contaminated soil after amendment with composted cow manure and poultry litter - Bushra Haroon; Muhammad Irshad; Farhan Hafeez; Arshid Pervez; Faridullah (Arabian Journal of Geosciences, 2019)

Organelle DNA contents and starch accumulation in potato tubers - Suyan Niu; Guodong Zhang; Xiubao Li; Muhammad Haroon; Huaijun Si; Guoqiang Fan; Xiu-Qing Li (Theoretical and Applied Genetics, 2019)

Rapid Screening of Potato Cultivars Tolerant to Nitrogen Deficiency Using a Hydroponic System - Xiaofang Xie; Xiu-Qing Li; Bernie J. Zebarth; Suyan Niu; Ruimin Tang; Helen H. Tai; Benoit Bizimungu; Weiren Wu; Muhammad Haroon (American Journal of Potato Research, 2018)

Antimicrobial and antioxidant activities of a new metabolite from Quercus incana - Farah Gul; Khalid Mohammed Khan; Achyut Adhikari; Salman Zafar; Muhammad Akram; Haroon Khan; Muhammad Saeed (Natural Product Research, 2017)

Maximizing maize quality, productivity and profitability through a combined use of compost and nitrogen fertilizer in a semi-arid environment in Pakistan - Shahid Iqbal; Christian Thierfelder; Haroon Zaman Khan; Hafiz Muhammad Rashad Javeed; Muhammad Arif; Muhammad Shehzad (Nutrient Cycling in Agroecosystems, 2017)

Prospective study of avian influenza H9 infection in commercial poultry farms of Punjab Province and Islamabad Capital Territory, Pakistan - Mamoona Chaudhry; Maqbool Ahmad; Hamad Bin Rashid; Bakhat Sultan; Haroon Rashid Chaudhry; Aayesha Riaz; Muhammad Shabir Shaheen (Tropical Animal Health and Production, 2017)

Drought monitoring and performance evaluation of MODIS-based drought severity index (DSI) over Pakistan - Muhammad Athar Haroon; Jiahua Zhang; Fengmei Yao (Natural Hazards, 2016)

Biofunctional properties of Eruca sativa Miller (rocket salad) hydroalcoholic extract - Khushbakht Sultan; Muhammad Zakir; Haroon Khan; Abdur Rauf; Noor Ul Akber; Murad Ali Khan (Natural Product Research, 2016)

Anti-tumour-promoting and thermal-induced protein denaturation inhibitory activities of β-sitosterol and lupeol isolated from Diospyros lotus L. - Abdur Rauf; Ghias Uddin; Haroon Khan; Muslim Raza; Muhammad Zafar; Harukuni Tokuda (Natural Product Research, 2016)

Antimicrobial and inhibition on heat-induced protein denaturation of constituents isolated from Polygonatum verticillatum rhizomes - Haroon Khan; Muhammad Saeed; Abdur Rauf; Muhammad Atif Khan; Naveed Muhammad (Natural Product Research, 2015)

First evidence of the analgesic activity of govaniadine, an alkaloid isolated from Corydalis govaniana Wall. - Naveed Muhammad; Ram Lal Shrestha; Achyut Adhikari; Abdul Wadood; Haroon Khan; Amir Zada Khan; Francesco Maione; Nicola Mascolo; Vincenzo De Feo (Natural Product Research, 2015)

Thymoquinone and Vitamin C Attenuates Pentylenetetrazole-Induced Seizures Via Activation of GABAB1 Receptor in Adult Rats Cortex and Hippocampus - Ikram Ullah; Haroon Badshah; Muhammad Imran Naseer; Hae Young Lee; Myeong Ok Kim (NeuroMolecular Medicine, 2015)

History and Origin of Russet Burbank (Netted Gem) a Sport of Burbank - Paul C. Bethke; Atef M. K. Nassar; Stan Kubow; Yves N. Leclerc; Xiu-Qing Li; Muhammad Haroon; Teresa Molen; John Bamberg; Max Martin; Danielle J. Donnelly (American Journal of Potato Research, 2014)

Population dynamics of citrus leaf miner on different varieties of citrus in correlation with abiotic environmental factors in Sargodha District, Punjab, Pakistan - Irfan Mustafa; Muhammad Arshad; Abdul Ghani; Iftikhar Ahmad; Abu Bakar Muhammad Raza; Farzana Saddique; Saira Asif; Mobushir Riaz Khan; Haroon Ahmed (Phytoparasitica, 2014)

Effect of heavy metal pollution on mineral absorption in sunflower (Helianthus annuus L.) hybrids - Unaiza Aslam; Iftikhar Ahmad; Mumtaz Hussain; Ameer Khan; Abdul Ghani; Irfan Mustafa; Sabahat Jalal; Muhammad Anjum Aqeel; Saira Asif; Haroon Ahmed (Acta Physiologiae Plantarum, 2014)

Isolation of long-chain esters from the rhizome of Polygonatum verticillatum by potent tyrosinase inhibition - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Izhar-ul-Haq; Naveed Muhammad; Rukhsana Ghaffar (Medicinal Chemistry Research, 2013)

Synthesis, spectroscopic, and biological evaluation of some levofloxacin metal complexes - Najma Sultana; Muhammad Saeed Arayne; Syeda Bushra Shakeb Rizvi; Urooj Haroon; Muhammad Ahmed Mesaik (Medicinal Chemistry Research, 2013)

Evaluation of n-hexane extract of Viola betonicifolia for its neuropharmacological properties - Naveed Muhammad; Muhammad Saeed; Haroon Khan; Ikramul Haq (Journal of Natural Medicines, 2013)

Antimalarial and free radical scavenging activities of rhizomes of Polygonatum verticillatum supported by isolated metabolites - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Inamullah Khan; Manzoor Ahmad; Naveed Muhammad; Afsar Khan (Medicinal Chemistry Research, 2012)

Comparative efficacy of diminazene diaceturate and diminazene aceturate for the treatment of babesiosis in horses - Hamad Bin Rashid; Mamoona Chaudhry; Haroon Rashid; Khalid Pervez; Muhammad Arif Khan; Asim Khalid Mahmood (Tropical Animal Health and Production, 2008)